Penerapan Kebijakan Pemerintah dalam Penegakan Hukum Usaha Pertambangan Minyak Bumi - Anggita Anggita (Savana, 2024)
Indonesia is rich in natural resources, including those found in the soil. This soil contains potential natural resources that can be exploited, for example, for oil mining, which is beneficial to humans. The purpose of this study is to identify how the implementation of government regulations, including Law Number 22 of 2001, functions to regulate mining business activities and protect the environment. Furthermore, this article analyzes the legal system through a case study of Decision Number 52/Pid.B/LH/2023/PN Mrt, which demonstrates law enforcement against misuse of business permits in the oil and gas sector. The research method employed is juridical-normative, drawing on literature, data and facts, and existing regulations. The results show that despite existing regulations, violations still occur, resulting in negative impacts on society and the environment. Therefore, increased supervision and law enforcement of oil and gas mining activities are needed to prevent potential violations.